Case of neuro‐Behçet's disease successfully maintained a remission using infliximab for 2 years. Issue 8 (3rd June 2013) - Kanemaru, Hisashi; Makino, Takamitsu; Jinnin, Masatoshi; Yonemitsu, Aya; Makino, Katsunari; Ihn, Hironobu
Abstract: Behçet's disease is a systemic inflammatory disorder with chronic remissions and relapses. Involvement of the central nervous system, called neuro‐Behçet's disease (NBD), is a serious complication. Although corticosteroids and immunosuppressive agents are used, there is no definite standard of treatment with long term‐effects for NBD. Here, we report a female case with NBD successfully treated by infliximab and corticosteroids for 2 years. Our report suggests treatment with infliximab may be effective for long‐term remission of NBD.